2017
DOI: 10.4038/cjs.v46i4.7472
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different media, medium strength and carbon sources on adventitious shoot cultures and production of bacoside A in <em>Bacopa monnieri</em>(L.)

Abstract: Abstract:Bacopa monnieri (L.) Wettst. (Plantaginaceae), commonly known as Brahmi, is used in Ayurveda as a medicinal herb, found throughout the Indian subcontinent in wet, damp and marshy areas. The herb yields pharmaceutically active compounds called bacosides. The current investigation was carried out to assess the potential for increasing biomass and the concentration of bacoside A from the in vitro regenerated shoots in different media (MS, B5, NN and N6), the strength of the MS medium (0.25, 0.50, 0.75, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Based on the growth vigor and morphological changes, the full-strength basal medium produced more vigorous shoots and greener leaves compared to half-strength basal medium which produced yellowish leaves. The full-strength basal medium was also found to be most effective for the micropropagation of Ocimum basilicum [ 24 ], Bacopa monnieri [ 25 ] and Thymus hyemalis [ 26 ]. All of these findings were in agreement with current findings, indicating the effectiveness of the full-strength MS basal medium for the medicinal plant studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the growth vigor and morphological changes, the full-strength basal medium produced more vigorous shoots and greener leaves compared to half-strength basal medium which produced yellowish leaves. The full-strength basal medium was also found to be most effective for the micropropagation of Ocimum basilicum [ 24 ], Bacopa monnieri [ 25 ] and Thymus hyemalis [ 26 ]. All of these findings were in agreement with current findings, indicating the effectiveness of the full-strength MS basal medium for the medicinal plant studied.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of 30 g/L sucrose was found to be the optimum for the growth of Thymus hyemalis compared to other types of carbon sources including glucose, fructose, mannitol and sorbitol [ 17 ]. The studies implied that a sucrose concentration higher than 30 g/L results in a decrease in the multiplication and growth rate of plants [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. These findings were in agreement with the present study in which 30 g/L of sucrose was established as the optimum for the growth of C. nutans .…”
Section: Discussionmentioning
confidence: 99%
“…Different levels of MS nutrient salts affected the shoot regeneration values of the plant. Similarly, it has been reported that different MS nutrient salts affect the growth-development or regeneration values of plants such as Mentha spicata L. [14], Bacopa monnieri (L.) [15] and Lophophora williamsii (Lem.) Coult.…”
Section: Resultsmentioning
confidence: 82%
“…In cassumunar ginger (Zingiber montanum), phenolic, flavonoid, tannin, alkaloid, saponin and steroid in induced micro-rhizomes using 6% sucrose were enriched over the natural rhizomes, whereas curcuminoid content was equal with natural rhizomes (Rajkumari and Sanatombi 2020). In Brahmi (Bacopa monnieri), mixed sucrose/maltose or glucose/ fructose was recommended for bacoside A production in the leaf tissues (Naik et al 2017). It is possible that total curcuminoids in mini-rhizome of acclimatized turmeric plants under iso-osmotic conditions may regulate in the long-term cultivation in ex vitro conditions.…”
Section: Discussionmentioning
confidence: 99%